1996
DOI: 10.1016/0020-7292(96)02673-2
|View full text |Cite
|
Sign up to set email alerts
|

High altitude and spontaneous preterm birth

Abstract: The enhanced formation of syncytial knots and cytotrophoblastic cells is a histological feature of placental hypoxia, which may be secondary to maternal hypoxia resulting from high altitude hypoxia. Since placental hypoxia is associated with an increased incidence of spontaneous preterm birth, we suggest that high altitude may be involved in the etiology of spontaneous preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The prevalence of total preterm birth in our study found to be (8%). Compared to other cities of Kingdom of Saudi Arabia, Similar findings were reported in Jazan (8.24%) [ 16 ], while others in Riyadh and Abha cities reported lower rates (5%) [ 17 , 18 ]. Compared to another part of the world, it is found to be more or less equal to that in Asian (9.8%) and European countries (6.7%), but less than in African (12.6%) and Vietnam (11.8%) [ 19 ].…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of total preterm birth in our study found to be (8%). Compared to other cities of Kingdom of Saudi Arabia, Similar findings were reported in Jazan (8.24%) [ 16 ], while others in Riyadh and Abha cities reported lower rates (5%) [ 17 , 18 ]. Compared to another part of the world, it is found to be more or less equal to that in Asian (9.8%) and European countries (6.7%), but less than in African (12.6%) and Vietnam (11.8%) [ 19 ].…”
Section: Discussionsupporting
confidence: 75%
“…Birth weight is reduced in high‐altitude infants, the rate of low birth weight is increased three‐ to fivefold, and maternal and neonatal mortality are markedly increased in the absence of optimal medical care 1 , 10 . Contributing to mortality are pre‐term labor and delivery, and an increase in hypertensive complications of pregnancy, especially preeclampsia, a serious and potentially fatal pregnancy‐related vascular disease 1 , 11 –17 . The underlying cause(s) of these suboptimal pregnancy outcomes at high altitude is still under investigation, but it is clear that altered vascular function during pregnancy resulting from the chronic stress of maternal hypoxia plays an important role in the reduced birth weights and increased complications observed 11 , 18 –20 …”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by clinical and experimental evidence; for example, pregnant women at high altitude (>4,000 meters above sea level) have triple chance of premature delivery than women living at sea level (12 versus 4%) [14]. Clinical conditions that are a reflection of placental ischemia, such as preeclampsia and fetal growth restriction, are frequently associated with premature onset of labor [5, 15].…”
Section: Uteroplacental Ischemia and Preterm Birthmentioning
confidence: 99%